MORPHOLOGICAL STATUS OF THE FEMALE ATHLETE FINALIST IN JUMPING DISCIPLINES AT THE BEIJING OLYMPICS - Ratko Pavlović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Morphological status of athletes is his, we can say, based on an identification card, which can be assigned to a particular constitutional type, and we also got information about his body height, body weight, BMI, and even used to analyze and age. Different constitutional types are present in the sport and are important in terms of targeting, selection and performance of a specific sport. This is particularly pronounced in the athletic sport where within athletics have many different types of athletes is constitutional requires a certain discipline. This paper analyzes the morphological status of female finalists in jumping events at the Olympic Games in Beijing 2008. The survey included 32 athletes who performed in the final of the measured variables to assess the morphological status: body height (AVIS), body mass (AMAS), derived body mass index (BMI) and age athletes (GOD). Applying basic statistical parameters (mean) made a comparative analysis of the applied variables based competitors that have passed certain conclusions.